PENGELOLAAN LAHAN BANTARAN SUNGAI BEDOG BERBASIS KOMUNITAS KARANG TARUNA GUNA MENDUKUNG PEMBANGUNAN BERKELANJUTAN - Julianto, Alfin -; Prasetyo, Iis (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2019)
ABSTRACT BEDOG RIVER MANAGEMENT BASED ON KARANG TARUNA COMMUNITIES TO SUPPORT SUSTAINABLE DEVELOPMENT This article is intended to discuss the process of community empowerment through the management of the Bedog River bank to support the pillars of sustainable development and great support from the management of the Bedog River in Munengan Hamlet, Sidoluhur Village, Godean District, Sleman Regency, Yogyakarta. This research is a descriptive qualitative research type. The subjects of this study were managers of fish ponds, youths of youth in Munengan Hamlet, Sidoluhur Village, and community of Munengan Hamlet, Sidoluhur Village. Data collection is done by using observation, interview, and documentation techniques. Data analysis techniques are data collection, data reduction, data presentation, and conclusion. The validity of research data using source triangulation and methods. The results of this study are: First, community empowerment through the Karang Taruna Bakti Community as an effort to manage the Bedog River bank starts from the process of awareness, reflection, and action on the management of river banks by planting water guava and passion fruit plants. Second, efforts to utilize riverbanks are beneficial for the riverbank environment and the community of Munengan Hamlet, Sidoluhur Village. The guava and passion fruit plants will produce fruit and the trees can preserve the ecology of the Bedog River banks from abrasion and support the pillars of sustainable development. Keywords: Management; Riverbanks; Sustainable Development; Karang Taruna Community